Financial Sector Assessment Program : Nigeria - Basel Core Principles for Effective Banking Supervision - International Monetary Fund; World Bank (World Bank, Washington, DC, 2013)
The assessment of the current state of the implementation of the Basel Core Principles (BCP) for effective banking supervision in Nigeria, against the BCP methodology issued by the Basel Committee on Banking Supervision (BCBS) in October 2006, was completed between August 27 and September 19, 2012, as part of a Financial Sector Assessment Program (FSAP) update, undertaken jointly by the Fund (IMF) and the World Bank, and reflects the regulatory and supervisory framework in place as of the date of the completion of the assessment. An assessment of the effectiveness of banking supervision requires a review of the legal framework, both generally and as specifically related to the financial sector, and a detailed examination of the policies and practices of the institutions responsible for banking supervision. Banking systems differ from one country to another, as do their domestic circumstances. The BCPs are capable of application to a wide range of jurisdictions whose banking sectors will inevitably include a broad spectrum of banks. The co-ordination of the activities of the Nigerian banking sector supervisory authorities is conducted under the aegis of the Central Bank of Nigeria (CBN)/Nigeria Deposit Insurance Corporation (NDIC) executive committee on supervision which should ensure that operations of the two supervisory authorities are coordinated to remove overlaps, avoid gaps and ensure adequate information sharing on issues of supervisory concern. The Financial Services Regulation Coordinating Committee (FSRCC) provides the platform for the co-ordination among and information sharing with regulatory authorities, inter alia with reference to financial sector stability, and supervision of financial conglomerates, financial holding companies and bank holding companies. The Nigerian economy has experienced a number of domestic and external shocks in recent years, which impacted the banking sector. The Nigerian economy emerged from the banking crisis, and has the potential to enjoy an extended period of strong economic growth.